2023
DOI: 10.4102/sajbm.v54i1.2937
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing electronic human resource management implementation in public organisations in an emerging economy: An empirical study

Abstract: Purpose: Governments in developing countries are riddled with operational inefficiencies. Many have turned to electronic service delivery to address these operational problems. With coronavirus disease 2019 (COVID-19) pandemic, the push for digitalisation has only got stronger. We use the technology acceptance model (TAM) and innovation diffusion model (IDM) to investigate the factors that influence the implementation of electronic human resource management (e-HRM) in selected public organisations in an emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Jayabalan et al (2020) also stressed that HRIS allows users such as HR managers to store and track many types of data that are useful to HRM. Amoako et al (2023) conducted a study and confirmed that perceived usefulness, self-efficacy, compatibility and enabling circumstances have substantial favorable influence on the e-HRM implementation. Model et al (2020) in a study discovered factors such as performance expectations, effort expectations and social influence as factors influencing the decisions to implement and use HRIS.…”
Section: Functions Of Human Resource Information Systemmentioning
confidence: 75%
“…Jayabalan et al (2020) also stressed that HRIS allows users such as HR managers to store and track many types of data that are useful to HRM. Amoako et al (2023) conducted a study and confirmed that perceived usefulness, self-efficacy, compatibility and enabling circumstances have substantial favorable influence on the e-HRM implementation. Model et al (2020) in a study discovered factors such as performance expectations, effort expectations and social influence as factors influencing the decisions to implement and use HRIS.…”
Section: Functions Of Human Resource Information Systemmentioning
confidence: 75%
“…A review of the body of research on e-HRM indicates that public and government organizations, especially those in developing nations, have not given e-HRM enough attention [15].…”
Section: Digital Human Resource Management Within Public Sector Entitiesmentioning
confidence: 99%
“…These variables were used under the organizational construct adapted from the TOE model. The variables explored and used in the study are Top Management Support (Al-Dmour et al, 2017), Financial Resources (Mokomane & Potgieter, 2020), Training (Dida, 2021), Relative Advantage (Amoako et al, 2023), and Change Management (Nugroho et al, 2022). The implementation of the HRIS consist of two variables namely: Acceptance (Rath & Das, 2020) and Effectiveness (Dey & Saha, 2020).…”
Section: Technology-organisation-environment (Toe) Frameworkmentioning
confidence: 99%